Rnf165/Ark2C enhances BMP-Smad signaling to mediate motor axon extension. - Claire E Kelly; Efstathia Thymiakou; James E Dixon; Shinya Tanaka; Jonathan Godwin; Vasso Episkopou (PLoS Biology)
Little is known about extrinsic signals required for the advancement of motor neuron (MN) axons, which extend over long distances in the periphery to form precise connections with target muscles. Here we present that Rnf165 (Arkadia-like; Arkadia2; Ark2C) is expressed specifically in the nervous system and that its loss in mice causes motor innervation defects that originate during development and lead to wasting and death before weaning. The defects range from severe reduction of motor axon extension as observed in the dorsal forelimb to shortening of presynaptic branches of the phrenic nerve, as observed in the diaphragm. Molecular functional analysis showed that in the context of the spinal cord Ark2C enhances transcriptional responses of the Smad1/5/8 effectors, which are activated (phosphorylated) downstream of Bone Morphogenetic Protein (BMP) signals. Consistent with Ark2C-modulated BMP signaling influencing motor axons, motor pools in the spinal cord were found to harbor phosphorylated Smad1/5/8 (pSmad) and treatment of primary MN with BMP inhibitor diminished axon length. In addition, genetic reduction of BMP-Smad signaling in Ark2C (+/-) mice caused the emergence of Ark2C (-/-) -like dorsal forelimb innervation deficits confirming that enhancement of BMP-Smad responses by Ark2C mediates efficient innervation. Together the above data reveal an involvement of BMP-Smad signaling in motor axon advancement.